2019
DOI: 10.20430/ete.v86i343.719
|View full text |Cite
|
Sign up to set email alerts
|

Efectos heterogéneos y distributivos del Seguro Popular sobre la oferta de servicios de salud en México

Abstract: Background: The effects that the expansion of the Seguro Popular (sp), Mexico's universal -according to the government-health insurance program, has had on the human and material resources needed to meet the new demand remain largely unexplored. It is a key piece in the quest for universal healthcare that we analyze in this paper. Methodology: Unlike previous evaluations, we use sanitary jurisdictions as units of analysis and operationalize sp's intervention as a continuous treatment indicator (relative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
2
Order By: Relevance
“…Public investment in health can then have important results, since market forces will not correct underinvestment in health, or will do so extremely slow (Lustig, 2017; Cylus & Al Tayara, 2021). Nevertheless, while SP has improved access to healthcare services, its achievements have not necessarily been equitable throughout the country (Huffman & Van Gameren, 2019), in part because financial resources have not effectively and efficiently been transformed into healthcare services due to the freedom states had in the spending of the federal resources they received (Nigenda et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public investment in health can then have important results, since market forces will not correct underinvestment in health, or will do so extremely slow (Lustig, 2017; Cylus & Al Tayara, 2021). Nevertheless, while SP has improved access to healthcare services, its achievements have not necessarily been equitable throughout the country (Huffman & Van Gameren, 2019), in part because financial resources have not effectively and efficiently been transformed into healthcare services due to the freedom states had in the spending of the federal resources they received (Nigenda et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the impact of SP found substantial reductions in out-of-pocket health expenditures (Avila-Burgos et al, 2012; Galárraga et al, 2010; Grogger et al, 2015), and generally positive effects on the utilization of healthcare services, such as consultations and doctor visits (Arenas et al, 2015; Parker et al, 2018), hospitalizations (Arenas et al, 2015), diagnostic tests (Knox, 2018; Parker et al, 2018), and treatment conditional on being sick (Parker et al, 2018; Rivera-Hernandez et al, 2016). Moreover, a positive impact on Mexico’s health resources has been reported (Huffman & Van Gameren, 2019) without negative impacts on formal labor markets (Del Valle, 2021). Regarding health incidence, the evidence is rather scarce; findings indicate improved diabetes control (Sosa-Rubí et al, 2009), reductions in maternal and infant mortality (Conti & Ginja, 2020; Knaul et al, 2012; Pfutze, 2014) as well as a lower risk of preterm births (Strouse et al, 2016), but no impact on mortality among those aged 60 or over (Conti & Ginja, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Suin Guaraca Luis Heriberto, Saetama Flores Tatiana Rosibel En México, el seguro popular ha tenido un impacto promedio positivo sobre los recursos de salud [15] y particularmente en los GBS excesivos que, a nivel nacional, han disminuido en un 36% [16], sobre todo en la población urbana [31]. En el caso de China, el plan médico cooperativo rural evitó que el 9.9% de los hogares sufriera catástrofes financieras y que el 7.7% de las familias se coloquen por debajo de la línea de pobreza, especialmente en el sector rural [12].…”
Section: Discussionunclassified
“…La seguridad social muestra un resultado positivo en cuanto al uso de los recursos de la salud, aunque no con una distribución equitativa [15,16]; la afiliación evitó catástrofes financieras y empobrecimiento de los hogares [12]; así mismo hubo resultados halagadores en la asequibilidad de los servicios de hospitalización y consulta preventiva que ayudaron a mantener niveles de salud adecuados [17].…”
Section: Introductionunclassified